Tradutores(as) e intérpretes de Libras e a triagem hospitalar: compreendendo seu papel e atuação no atendimento do paciente surdo - Carvalho, Samara de Souza (Universidade Federal de São Carlos, 2023)
This paper aims to discuss the role of the interpreter translator de Libras (TILS) in view of the need to assist deaf people in screening processes in emergency care at health centers and later referral to medical care. We had as a general objective analyze the technical and ethical aspects that must be present in the performance of the TILS during this screening, based on the considerations of a deaf person user of the public health network and a Libras interpreter who has already worked in this context. Therefore, for this qualitative research, we interviewed two participants - being a deaf person/patient and a professional interpreter of Libras - seeking to identify how this initial moment of reception in the health has been carried out with deaf people. The responses collected through of semi-structured interviews were analyzed using content analysis and organization into nuclei of meaning, seeking to emphasize the importance of strategies adopted to overcome linguistic differences and to achieve a good service in health centers in order to combat language barriers identified by the deaf person. As results, we highlight the lack of effective communication between healthcare professionals healthcare and deaf patients and we present some strategies used by health professionals caring for deaf patients, based on the report of the deaf patient (since TILS does not always work in this context), as well as strategies identified by the professional interpreter as those adopted for action in this sphere. In this sense, it is clear from from our interviews, that the health context presents challenges that are quite specific for interpretation for Libras, which points to the need specific training for the performance of TILS in the health sphere, given its complexity.
Libras translators and interpreters and hospital triage: understanding their role and performance in the care of deaf patients
Keywords: Triagem hospitalar; Atendimento em saúde; Pessoas surdas; Tradutoras/es e intérpretes de Libras; LINGUISTICA, LETRAS E ARTES::LETRAS; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA